REALIZING ANTI-BULLIYING THROUGH HABITUATION ACTIVITIES “SAYBER PANCANGAN DOA” AS AN EFFORT TO IMPROVE CHARACTER EDUCATION - Edy Prayoga; Sri Harini; Suci Hidayati (Fakultas Tarbiyah, Universitas Ibrahimy, 2023)
Post-pandemic online learning raises the problem of declining character values such as decreased self-confidence, concern for the environment, selfishness, and empathy for others. This makes educational institutions have the tough task to restore the identity of their students. One of the efforts made by the Head of SMKN 1 Turen Malang Regency to minimize the above problems is to carry out character education habituation activities called